PEMANFAATAN TUMBUHAN DAN LIMBAH RUMAH TANGGA SEBAGAI MEDIA PEMBELAJARAN PADA KELOMPOK ANAK - Herlina Menufandu; Nelly Lunga (JURNAL PENGABDIAN PAPUA, 2020)
Media had an important things as an object to got an affective study aims. It is needed by  childrens because they are in concrete think. Conveying infomation through media is help children to accepted and understood what they learn about. So it can be improve knowledge, attitude, and skill ability. Therefore through this community service, children creativity can be improved by utilize plants and house waste as learning media.Teoritical method, field survey, dan practice maked the media were the methods was used in this activity. Some plants such as cucurma, pitaya, red spinach, and pandanus were used as natural colour to added in toy candles, toy sand, and paint. Natural colour from plants is needed for children safety and also founded easly around.Keywords: Plants, house waste, children group